2017
DOI: 10.1183/13993003.00559-2017
|View full text |Cite
|
Sign up to set email alerts
|

Air pollution and subclinical interstitial lung disease: the Multi-Ethnic Study of Atherosclerosis (MESA) air–lung study

Abstract: We sought to determine whether ambient air pollution is associated with interstitial lung abnormalities (ILA) and high attenuation areas (HAA), which are qualitative and quantitative measurements of subclinical ILD on computed tomography. We performed analyses of 6813 community-based dwellers enrolled in the Multi-Ethnic Study of Atherosclerosis (MESA), a U.S.-based prospective cohort study. We used cohort-specific spatiotemporal models to estimate predictions of ambient pollution (PM2.5, NOx, NO2 and O3) at e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
71
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(76 citation statements)
references
References 33 publications
5
71
0
Order By: Relevance
“…Nevertheless, although more research is needed before drawing a causal relationship between air pollution and the development of IPF, this study provides the first evidence on the chronic effects of air pollution on the incidence of IPF and converges with previous work identifying air pollution as a risk factor for acute exacerbation and lung function decline in IPF patients [8][9][10]. These findings expand recent results from the Multi-Ethnic Study of Atherosclerosis (MESA) cohort, which reported that higher exposure to oxides of nitrogen and NO 2 increased risk of interstitial lung abnormalities and the 6-year progression of high attenuation areas, two measurements of subclinical interstitial lung disease [11]. From a broader point of view, this study adds to the literature showing association between air pollution exposure and the development of chronic lung diseases such as asthma [12], chronic obstructive pulmonary disease [13] or lung cancer [14].…”
supporting
confidence: 85%
“…Nevertheless, although more research is needed before drawing a causal relationship between air pollution and the development of IPF, this study provides the first evidence on the chronic effects of air pollution on the incidence of IPF and converges with previous work identifying air pollution as a risk factor for acute exacerbation and lung function decline in IPF patients [8][9][10]. These findings expand recent results from the Multi-Ethnic Study of Atherosclerosis (MESA) cohort, which reported that higher exposure to oxides of nitrogen and NO 2 increased risk of interstitial lung abnormalities and the 6-year progression of high attenuation areas, two measurements of subclinical interstitial lung disease [11]. From a broader point of view, this study adds to the literature showing association between air pollution exposure and the development of chronic lung diseases such as asthma [12], chronic obstructive pulmonary disease [13] or lung cancer [14].…”
supporting
confidence: 85%
“…Interstitial lung diseases are a group of diffuse parenchymal lung disorders [15] that are related to occupational or ambient air pollution exposures [16]. Pulmonary sarcoidosis is an inflammatory lung disorder associated with ethnicity and latitude [17].…”
Section: Discussionmentioning
confidence: 99%
“…Air pollution has been a serious public health problem over the past decades all over the world. [1][2][3][4] Previous studies indicated that at least half of the population lived in areas which did not satisfy the World Health Organization (WHO) guidelines-24-hours mean of 50 μg/m 3 for PM 10 (particulate matter <10 μm) and 24-hours mean of 25 μg/m 3 for PM 2.5 (particulate matter <2.5 μm). 5 Pollutants of air pollution also include gaseous substances, namely ozone, nitrogen oxides and sulphur dioxide.…”
Section: Introductionmentioning
confidence: 99%